Intention to use online meeting applications during Covid-19 pandemic: A Technology Acceptance Model perspective - Gilang Puspita Rini; Imroatul Khasanah (Jurnal Manajemen dan Pemasaran Jasa, 2021)
This research aims to add to the repertoire on the knowledge of perceived risk effect on the intention to use online meeting applications during the COVID-19 pandemic. Data were obtained from 186 respondents using the questionnaire instrument, which had been tested, for validity and reliability. The obtained data were analyzed using the Structural Equation Model. Based on the data testing, it was found that all hypotheses in this research were accepted. Therefore, the intention to use online meeting applications was most affected by perceived ease of use comparing to perceived risk. The results showed that developingcompanies increased perceived ease of use, hence the technology is easily accepted by consumers.